The Motor Coordination as a Creation Device: a somatic approach in contemporary dance - Bianchi, Paloma; Nunes (Universidade do Estado de Santa Catarina, UDESC, Florianópolis, Brazil) Sandra Meyer (Revista Brasileira de Estudos da Presença, 2022)
This article postulates that Somatic Education integrates similar issues related to perception in both cognitive science and philosophy. It also indicates that somatic approaches can expand their area of action, overcoming their original role in health maintenance and technical improvement, to reside in the field of research and creation in dance. In order to strength the relationship between dance and somatic education, this article seeks to address some principles of Béziers and Piret’s Motor Coordination study and points out their possible unfolding in research and creation in dance through perception.